Supplier relationship management in public procurement of Bangladesh: the case of Information and communication Technology (ICT) division - Islam, Md Tariqul (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2022.